Feeding practices in sheep stockbreeding in the Algerian steppe (M’Sila region): Current situation and prospects for improvement - Hadbaoui I.; Senoussi A.; Huguenin J. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The Algerian steppe covers 20 million hectares and is located between the isohyets of 100 and 400 mm/year. It is home to 17 million sheep (MADRP, 2016). For the past 50 years, it has undergone many changes and transformations resulting from the stockbreeding management that contributed to a decline in forage productivity and in the surface area of steppe pastures. Therefore, the steppe pasture covers only 30 to 40% of the animal’s feed requirements. To face this situation, stockbreeders are adopting various feeding strategies. Our objective was to assess the feeding practices adopted by the herders in M’Sila region. This region has 1 million ha of rangelands and hosts 1.63 million sheep heads (DSA, 2016). One hundred herders, from the different breeding systems and different pastoral areas, were investigated by technical-organizational approaches. The analysis of field interviews revealed the presence of two feeding calendars, involving different feed sources (concentrate feeds, cultivated forages, and cereal co-products). Although the supplementation with concentrate feeds is a common practice to meet animal needs (about 40% of ration), there are new feeding trends based on the direct consumption of green fodder (barley, oat and alfalfa). The choice of feeding strategies depends on the socio-economic and agricultural considerations of each herder (herd size, financial capacity, farming practice, income diversification, etc.).
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)